Pengaruh Sikap Prokrastinasi terhadap Motivasi Berprestasi Mahasiswa Program Studi Pendidikan Akuntansi Universitas Sebelas Maret - Sari, Alifah Puspita; Tata Ratu Kencana; Irfan Setiawan (JURNAL ILMIAH NUSANTARA, 2025)
This study aims to analyze the effect of academic procrastination on achievement motivation among Accounting Education students at Sebelas Maret University. A quantitative approach with causal comparative design was employed. Data were collected through online questionnaires from 30 students using Likert scale instruments. The results reveal that academic procrastination has differential effects depending on students' motivation levels. For low-motivation students, procrastination showed negative effects (-0.27), while for high-motivation students it demonstrated positive impacts (0.14). These findings indicate that the relationship between procrastination and achievement motivation is dynamic and contextual. The study provides important implications for developing tailored procrastination intervention strategies based on students' motivational profiles.